Improving Lathe Efficiency through Overall Equipment Effectiveness and Automatic Maintenance Methods - Pangestu, Bilal Setiyo; Joumil Aidil Saifuddin (Advance Sustainable Science Engineering and Technology, 2025)
In the current industrial era, operational efficiency is key for companies. Machining service providers can be seen from the number of workshops. At CV. XYZ has a lathe problem, there is no method for maintenance. Therefore, the purpose of this study is to calculate machine maintenance in companies using the Autonomous Maintenance (AM) method. From the calculation results obtained during January-June 2024, the highest average OEE value was in May 88.82%, Availability Rate parameters 88.76%, Performance Rate 99.28%, Rate of Quality 100%. The lowest average OEE value occurred in January 52.11% with Availability Rate parameters 76.44%, Performance Rate 90.66%, Rate of Quality 75%. From these results, it is necessary to have machine maintenance with indications for each component: cleaning the dynamo regularly, ensuring the on-off button is connected which is expected to increase effectiveness, extend machine life, and reduce maintenance costs.